Phosphate solubilizing microorganisms: a sustainability strategy to improve urban ecosystems - Feng, Yang; He, Jing; Zhang, Hongchen; Jia, Xiaolin; Hu, Youning; Ye, Jianqing; Gu, Xinyuan; Zhang, Xinping; Chen, Haoming (Frontiers in Microbiology, 2024)
Intensification of urban construction has gradually destroyed human habitat ecosystems. Plants, which serve as the foundation of ecosystems, require green, low-cost, and effective technologies to sustain their growth in stressful environments. A total of 286 keywords and 10 clusters from the bibliometric analysis of 529 articles (1999-2023) indicate the increasing importance of research on microbial functionality in landscape ecosystems. Phosphorus-solubilising microorganisms (PSMs) also improve plant disease resistance, adaptability, and survival. PSMs are widely used to promote plant growth and improve ecological quality. They can increase the availability of phosphorus in the soil and reduce the dependence of plants on chemical fertilisers. Microorganisms regulate phosphorus as key tools in landscape ecosystems. Most importantly, in urban and rural landscape practices, PSMs can be applied to green spaces, residential landscapes, road greening, and nursery planting, which play significant roles in improving vegetation coverage, enhancing plant resistance, improving environmental quality, and mitigating the heat island effect. PSMs are also helpful in restoring the ecological environment and biodiversity of polluted areas, such as brownfields, to provide residents with a more liveable living environment. Therefore, the multiple efficacies of PSM are expected to play increasingly important roles in the construction of urban and rural landscape ecosystems.